Ignition of coal-water fuel particles under the conditions of intense heat; Applied Thermal Engineering; Vol. 106 - Salomatov V. V. Vladimir Vasiljevich; Kuznetsov G. V. Geny Vladimirovich; Syrodoy S. V. Semen Vladimirovich; Gutareva N. Yu. Nadezhda Yurievna (2016, 2016)
Title screen